Antibiotic Resistance Pattern of Pasteurella multocida of Avian Origin - Sriram, Vamshi Krishna; Nagaleekar, Viswas Konasagara; Agarwal, Rajesh Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study documents the antibiotic resistance phenotypes among 134 strains of Pasteurella multocida isolated from chicken,  ducks, turkeys, pigeons and geese in India. P. multocida type A was found to be predominant capsular type causing fowl cholera. The  isolates were resistant to sulphadiazine (90.3%), tetracycline (32%), pefloxacin (20.9%), ciprofloxacin and spectinomycin (18.6%). The  sensitivity pattern indicates that the gentamicin was most effective (98.5%), followed by amoxyclav (97.7%), ampicillin (93.3%) and  ceftriaxone (94%). Sulfamethoxazole-trimethoprim was found to be effective against 83.5% of the isolates. Erythromycin and enrofloxacin  exhibited intermediate sensitivity of 57% and 67.1%, respectively. Also 23.8% isolates were found to be multidrug resistant and was  statistically significant (p
Keywords: Antibiotic resistance; India; Pasteurella multocida; Poultry